American Televangelism and Participatory Cultures Fans, Brands, and Play With Religious "Fakes" - Bekkering, Denis J. (Contemporary Religion and Popular Culture, 2018)
This book examines unintended participatory cultures and media surrounding the American televangelists Robert Tilton and Tammy Faye Bakker-Messner. It brings to light heavily ironic fan followings; print, audio, and video projects; public access television parodies; and other comedic participatory practices associated with these controversial preachers from the 1980s onwards. For Tilton's ministry, some of these activities and artifacts would prove irksome and even threatening, particularly an analog video remix turned online viral sensation. In contrast, Bakker-Messner's "campy" fans - gay men attracted to her "ludicrous tragedy" - would provide her unexpected opportunities for career rehabilitation. Denis J. Bekkering challenges "supply-side" religious economy and branding approaches, suggestions of novelty in religion and "new" media studies, and the emphasis on sincere devotion in research on religion and fandom. He also highlights how everyday individuals have long participated in public negotiations of Christian authenticity through tongue-in-cheek play with purported religious "fakes.".